2020
DOI: 10.1071/ch19482
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Fatty Alcohol Ether Carboxylic Ester Surfactant and its Performance in an Anionic/Non-Ionic Mixed System

Abstract: A salt-type fatty alcohol ether carboxylic ester (AECE-Na) surfactant with both anionic and non-ionic characteristics was synthesised using a fatty alcohol ether (AEO) and succinic anhydride. Compared with traditional synthetic methods, neither irritating substances (chloroacetic acid and chloroacetate) nor precious metals (Pt and Pd) were used in the synthesis, which is a simple, economic, and green method. FT-IR and 1H NMR spectroscopies and MALDI TOF mass spectrometry were used to prove the molecular struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Surfactants are widely used in various fields because of their special properties. However, as commercial products, single surfactant cannot meet the needs of reality, so it is particularly important to study the properties of mixed surfactants [1–3] . Moreover, through a series of studies, it is found that the performance of the mixed surfactants are better than that of single surfactant [4,5] …”
Section: Introductionmentioning
confidence: 99%
“…Surfactants are widely used in various fields because of their special properties. However, as commercial products, single surfactant cannot meet the needs of reality, so it is particularly important to study the properties of mixed surfactants [1–3] . Moreover, through a series of studies, it is found that the performance of the mixed surfactants are better than that of single surfactant [4,5] …”
Section: Introductionmentioning
confidence: 99%